Recent Update on Perovskite/Organic Tandem Solar Cells - Т. Серикова; Г. Бижанова; Ханлин Ху; Энни Нг (Қарағанды университетінің хабаршысы. Физика сериясы)
The emergence of multiple-junction photovoltaics (PVs) has presented a remarkable opportunity to overcome the Shockley-Queisser limit of single-junction solar cells. Recently, perovskite solar cells (PSCs) and organic photovoltaics (OPVs) are two of the most promising new-generation PVs, which have gained widespread attention in the PV community due to their exceptional rapid growth in their power conversion efficiencies (PCEs). Combining PSCs and OPVs in tandem structures offers numerous advantages, such as the ability to tune the bandgap of absorbers to regulate the absorption bands and enhance transparency. The use of thin-film technology ensures that the devices are lightweight and flexible, which is particularly advantageous for certain applications. Furthermore, both PSCs and OPVs are low-cost, making them attractive for large-scale deployment in the future. These advantages will make PSC/OPV tandem devices promising for applications beyond traditional silicon-based PVs. This review provides an up-to-date account on the recent progress of PSC/OPV tandem PVs. The state-of-the-art fabrication techniques and material engineering on the properties of PSC and OPV sub cells as well as their functional layers are discussed. A perspective guidance is also given to direct the future development of this type of tandem PVs. This paper provides an insight into the development of PSC/OPV tandem PVs, providing researchers with a roadmap to advance this technology further and unlock its full potential in the field of renewable energy.